ANALYSIS OF THE EFFECT OF CHANGES IN VEGETATION COMPOSITION AND BUILD UP AREA TO SURFACE TEMPERATURE (STUDY CASE: TEGAL CITY) - Chandra Satria Ajie Wicaksono; Abdi Sukmono; Firman Hadi (Jurnal Geodesi UNDIP, 2021)
The population growth in big cities continues to increase day by day. This phenomenon is what encouragesthe government and developers to work together to provide a decent place to live with other supporting facilities. Adevelopment journey impacts changes in surface temperature, air temperature, and global radiation. Changes intemperature are needed to see the great influence of changes in vegetation area and built-up areas on changes intemperature that occur. Surface temperature processing uses the Land Surface Temperature (LST) algorithm andland cover processing in the form of vegetation, built-up areas, waters and vacant land uses the guidedclassification of the maximum likelihood method. The calculation of land cover dominance in Tegal City uses alandscape matrix with the Largest Patch Index (LPI) calculation algorithm. Analysis of changes in vegetation, built-up area and surface temperature based on a multi-scale grid with a grid size of 20 "x20". The results showed thatthere were changes in the area of vegetation, built-up area and surface temperature. The multiple linear regressionequation in 2013 produces the equation Y = 25.521 - 0.014X1 + 0.056X2 with a value of R² = 0.715. In period 2017resulted in the equation Y = 27.732 + 0.008X1 + 0.052X2 with a value of R² = 0.734 and in 2020 the equation Y =29.381 - 0.002X1 + 0.055X2 with a value of R² = 0.736. The resulting multiple linear regression results that there isan effect of changes between vegetation and built-up areas on surface temperature.